Preliminary 19F-MRS Study of Tumor Cell Proliferation with 3′-deoxy-3′-fluorothymidine and Its Metabolite (FLT-MP). (26th September 2017) - Ko, In Ok; Jung, Ki-Hye; Kim, Mi Hyun; Kang, Kyeung Jun; Lee, Kyo Chul; Kim, Kyeong Min; Noh, Insup; Lee, Yong Jin; Lim, Sang Moo; Kim, Jung Young; Park, Ji-Ae
Abstract : The thymidine analogue 3′-deoxy-3′-[ 18 F]fluorothymidine, or [ 18 F]fluorothymidine ([ 18 F]FLT), is used to measure tumor cell proliferation with positron emission tomography (PET) imaging technology in nuclear medicine. FLT is phosphorylated by thymidine kinase 1 (TK1) and then trapped inside cells; it is not incorporated into DNA. Imaging with 18 F-radiolabeled FLT is a noninvasive technique to visualize cellular proliferation in tumors. However, it is difficult to distinguish between [ 18 F]FLT and its metabolites by PET imaging, and quantification has not been attempted using current imaging methods. In this study, we successfully acquired in vivo F 19 spectra of natural or nonradioactive 3′-deoxy-3′-fluorothymidine ([ 19 F]FLT) and its monophosphate metabolite (FLT-MP) in a tumor xenograft mouse model using 9.4T magnetic resonance imaging (MRI). This preliminary result demonstrates that 19 F magnetic resonance spectroscopy (MRS) with FLT is suitable for the in vivo assessment of tumor aggressiveness and for early prediction of treatment response.